Robust associations of emotional intelligence with human flourishing: A second-order meta-analysis - Tyler J. Robinson; Ethan Zell (Proceedings of the National Academy of Sciences, 2026)
Emotional intelligence (EI) is an umbrella term that has been used to describe i) the ability to reason accurately about emotions and use emotions to augment thought processes, ii) a constellation of traits reflecting social and emotional functioning, or iii) a mix of relevant abilities and traits. Research on EI has expanded considerably since the 1990s, resulting in dozens of meta-analyses on its relationship with various indices of flourishing (e.g., psychological well-being, adaptive traits, and adaptive functioning in the classroom and workplace). In this second-order meta-analysis, we synthesized data from 62 meta-analyses including over 3,000 studies and 1 million participants. Our findings suggest a robust association between human flourishing and an overall index of EI, r = 0.28, 95% CI [0.25, 0.31], as well as separate indices of ability, trait, and mixed EI. Favorable EI associations were found across several outcome categories (e.g., cognitive abilities, psychological adjustment, mental health, workplace outcomes) as well as age and cultural groups. Nevertheless, effect sizes were most pronounced for self-report EI measures, especially when flourishing was likewise measured subjectively. Further, there was substantial heterogeneity of EI-flourishing effect sizes. We recommend that future research identify additional moderators of EI-flourishing associations. We also discuss ongoing debates about the conceptualization of EI and suggest that future work consider alternative EI schemes.